Spatial genetic structure of dusky dolphin, Lagenorhynchus obscurus, along the argentine coast: preserve what scale? - Loizaga de Castro, Rocio (2015)
The dusky dolphin (Lagenorhynchus obscurus) represents one of the most abundant species of small cetacean in Argentine waters. During the 1980s and 1990s, high levels of incidental mortality in purse and trawl fisheries were documented, and in recent decades tourism activities have been added as a potential source of disturbance. The study objectives were to identify spatial genetic structure and regional genetic patterns of dusky dolphins along the Argentine coast. The variation of 413bp of the control region of 119 individuals over six locations spread along 2800 km (38°40'S to 54°30'S) was examined. Spatial genetic analyses, SAMOVA, genetic landscape shapes and autocorrelation analyses were conducted. The most probable configuration was K=2, island population vs. continental populations (FCT = 0.774) and the spatial autocorrelation analysis showed a strong regional genetic structure, defining an operational unit at < 50 km. The results provide valuable information that should be taken into account in the development of conservation strategies and management of the species; making the efforts focus on conserving vulnerable dusky dolphin groups by protecting their preferred coastal shallow habitat and by monitoring and regulating the dolphin watching and fishing activities, acting upon local populations along the Argentine coast.